Mechanisms of Action of Topical Corticosteroids in Psoriasis. (20th November 2012) - Uva, Luís; Miguel, Diana; Pinheiro, Catarina; Antunes, Joana; Cruz, Diogo; Ferreira, João; Filipe, Paulo
Abstract : Psoriasis is a lifelong, chronic, and immune-mediated systemic disease, which affects approximately 1–3% of the Caucasian population. The different presentations of psoriasis require different approaches to treatment and appropriate prescriptions according to disease severity. The use of topical therapy remains a key component of the management of almost all psoriasis patients, and while mild disease is commonly treated only with topical agents, the use of topical therapy as adjuvant therapy in moderate-to-severe disease may also be helpful. This paper focuses on the cutaneous mechanisms of action of corticosteroids and on the currently available topical treatments, taking into account adverse effects, bioavailability, new combination treatments, and strategies to improve the safety of corticosteroids. It is established that the treatment choice should be tailored to match the individual patient's needs and his/her expectations, prescribing to each patient the most suitable vehicle.